Calycosin suppresses TGF-β-induced epithelial-to-mesenchymal transition and migration by upregulating BATF2 to target PAI-1 via the Wnt and PI3K/Akt signaling pathways in colorectal cancer cells - Qun Wang; Weijun Lu; Tao Yin; Li Lu (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Objectives To determine whether the upregulation of basic leucine zipper ATF-like transcription factor 2 (BATF2) by calycosin suppresses the growth and epithelial-to-mesenchymal transition (EMT) in human colorectal cancer (CRC) cells. Method Cells were cultured and treated with different concentrations of calycosin for different periods of time. Protein and mRNA expression was determined by western blotting and quantitative PCR. Cell migration was assessed by Transwell experiments. Co-immunoprecipitation and luciferase assays were used to analyze the association between BATF2 and plasminogen activator inhibitor-1. (PAI-1). Cell apoptosis was determined by flow cytometry; β-catenin cellular localization was visualized by immunofluorescent staining. Results Calycosin up-regulated the expression of BATF2 via the signal transducer and activator of transcription 3 (STAT3) pathway, which was antagonized by transforming growth factor beta (TGF-β), calycosin promoted the cell apoptosis and growth inhibition via phosphoinositide 3-kinase (PI3K)/Akt pathway. TGF-β promoted cell growth, which was inhibited by calycosin regulating the expression of proliferating cell nuclear antigen (PCNA) via the phosphoinositide 3-kinase pathway. TGF-β suppressed expression of BAX via the phosphoinositide 3-kinase pathway but induced cell apoptosis .calycosin enhanced the effect of TGF-β on cell apoptosis,In addition, calycosin suppressed TGF-β-induced cell migration by increasing BATF2 to target PAI-1. TGF-β-induced EMT was inhibited by calycosin in human CRC LoVo and HCT116 cell lines via the Wnt signaling pathway. Conclusions The induction of BATF2 by calycosin may be a feasible therapeutic option for CRC. Graphical Abstract .